A Internalizing Exemplary Values Through Kiai Leadership: A Study of KH. A. Zubairi Mz in Building Santri's Learning Motivation - Aribuddin, Aribuddin; Zinawar, Zinawar (Magister’s Program in Islamic Education Postgraduate Program, Universitas Annuqayah Sumenep, 2024)
This study examines the moral exemplarity (uswah hasanah) of KH. A. Zubairi Mz and its role in fostering santri's learning motivation at Pondok Pesantren Nasy'atul Muta'allimin. Employing a qualitative field research design with a descriptive-analytic approach, this study draws on Edwin Guthrie's behaviorist theory to analyze the underlying factors and manifestations of his exemplary conduct, as well as the ways in which santri internalize his values. Data were collected through observation, interviews, and documentation. The findings reveal that KH. A. Zubairi Mz's moral exemplarity was fundamentally rooted in his profound love of knowledge (ḥubb al-'ilm). Its manifestations include sincere teaching, cultivating familial bonds with santri, heart-centered pedagogy through persistent supplication, and consistent practice of Islamic humility (tawāḍuʿ). Santri internalized these values through scholarly engagement, oral testimonies from senior santri, preservation of his legacy, and written documentation of his life and teachings. This study concludes that moral exemplarity grounded in sincere spiritual values constitutes a powerful mechanism for fostering intrinsic learning motivation within the pesantren educational tradition.